Evaluation Of Inverse Kinematics For Quadruped Robot With Accelerometer Sensor - Ahmad Iqbal Nasrudin; Khairul Anam; M. Agung Prawira N (Jurnal Rekayasa Elektrika, 2019)
Quadruped robot is one of the types of robots that move using legs 4 compiled by some of the servo motor as a driving force on each foot ft the DOF is used. However, problems arise when this robot is confronted on the inclined plane, because the burden is borne out every servo motor on the feet will be different, so can make a fast servo motor damaged. This research was conducted on the design of the quadruped robot system for stability on the inclined plane using the accelerometer sensor and the application of the inverse kinematics method with PID control of Ziegler-Nichols. The results of tests obtained response robots in stabilizing the body when faced with the inclined plane with some degree of slope of the pitch and roll. In this research was conducted some test for quadruped robot: static Testing robot against the angel of the pitch in the standby retrieved response average robot in stabilizing the body is 245 ms, static Testing robot against the angle of roll in standby retrieved response average robot in stabilizing the body is 280 ms, dynamic Testing robot against the roll and pitch in standby retrieved response average robot in stabilizing the body is 8 seconds, Static Testing robot to stabilizing the body against the angel of roll in running the largest robot oscillations obtained 10 degrees, dynamic Testing robot to stabilizing the body against the angle of roll in run retrieved response average robot in stabilizing the body is 490 ms.